A Novel IGBT-Based Silicone Carbide Rectifier Design for Improved Energy Efficiency in Telco Data Centers - Fatih Yalçın; Hüseyin Köse; Asuman Savaşcıhabeş (Energies)
This study presents a novel topology designed to enhance the energy efficiency and quality of IGBT-based high-frequency rectifiers, which are commonly used to supply the high DC power required in industrial applications. In the proposed design, traditional silicon semiconductors are replaced with advanced SiC semiconductors, resulting in reduced switching losses and improved energy quality due to higher frequency switching. The new topology also offers solutions to challenges such as inrush current, reverse energy flow, and high DC output voltage issues typically encountered in IGBT-based rectifiers. The goal is for this topology to maximize efficiency and applicability. The proposed design is simulated in the Simulink environment, with the results presented in the findings section. To highlight the advantages of the new topology, the electrical parameters of the widely used three-phase full-bridge IGBT rectifier topology are employed for comparison.